AKTIVITAS ANTIMIKROBA EKSTRAK DAUN JAMBU BIJI DARI BEBERAPA KULTIVAR TERHADAP Staphylococcus aureus ATCC 25923 DENGAN "HOLE-PLATE DIFFUSION METHOD" - Farida Lanawati Darsono; Stephanie Devi Artemisia (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
A study has been performed on the antimicrobial activities of “jambu biji” (Psidium guajava Linn) leaves from several cultivars (red, white and yellow cultivar) against Staphylococcus aureus ATCC 25923 representing the Gram positive bacteria. The reason for conducting this research is that the leaves of “jambu biji” are frequently used in traditional medicine as a remedy against diarrhoea. The hole-plate diffusion method was used for conducting the antimicrobial activity test with antibiotics (Ampicilline trihidrat) as reference standards. The extracts of “jambu biji” for each cultivar were obtained by reflux with ethanol 96%. The concentrations of the extracts applied to the holes were 10%, 20%, and 30% w/v, the extracts were reconstituted with tween 80 and ethanol 96%. Based on the result of the study, it can be concluded that the extract of “jambu biji” from each cultivar with the concentration of 10%, 20%, and 30% w/v showed antibacterial activities against Staphylococcus aureus ATCC 25923. The result obtained statictically evaluated using Anava Factorial 3×3 and furthery tested for significancy (α = 0.05). Based on the results of study, it can be concluded that the extract of jambu biji leaves from red cultivar, white cultivar and yellow cultivar showed antibacterial activities against Staphylococcus aureus ATCC 25923.